The Moral Virtues of Students as Expected by the Administrators and Instructors of Bangkokthonburi University - อรอมรรัตน์, รสรินทร์ (Journal of Humanities and Social Sciences, Rajapruk University, 2019)
The purposes of this research were to; 1) analyze the moral virtues of students as expected by the administrators and instructors of Bangkokthonburi University, 2) compare the moral virtues of students as expected by the administrators and instructors of Bangkokthonburi University in education and other fields, and 3) propose guidelines for performing instructional activities to instill the Bangkokthonburi University students with moral virtues so that they possess desirable characteristics. The informants of the study were divided into 2 groups including 20 administrators and 5 instructors totaling 25 persons. Quality research method was utilized for this study by documentary study, in-depth interview and focus group by 5 experts. The instrument used for this study was semi-structured interview. The collected data were analyzed by using data classification, data comparison and inductive conclusions. The research findings were as follows: The moral virtues of students as expected by the administrators and instructors of Bangkokthonburi University including 1) keeping disciplines 2) integrity 3) others 4) politeness 5) kindness and 6) diligence. According to the comparison results of the moral virtues of students as expected by the administrators and instructors of Bangkokthonburi University in education and other fields, the points of view of the 2 groups of informants were different especially in being persistent to studying, including integrity, politeness and others. The proposed guidelines for performing instructional activities to instill Bangkokthonburi University students with moral virtues to possess desirable characteristics included 1) curriculum: every curriculum should emphasize more academic content together with incorporating moral virtues in lessons as well as encouraging the students to have their self-esteem and awareness in significance of professionals 2) teaching and learning process: active-learning by cooperative learning and self-directed learning should be performed through performance-based learning and sources of learning should increase and 3) measurement and evaluation: the emphasis should be on assessing academic and affective domain activities which are accurately and precisely evaluated.